TECHNOLOGY FOR THE DEVELOPMENT OF INTERCULTURAL COMMUNICATION IN TEACHING FOREIGN LANGUAGES - Khamzaev, Otakhon (Журнал иностранных языков и лингвистики, 2021)
The article deals with the relevance of intercultural communications of students. When the students are prepared to solve the problems in intercultural communication between representatives of different cultures, to understand the values and generally accepted norms of behavior, they can avoid misunderstandings, inadequate perception of the behavior and potential conflicts that necessarily arise due to incorrect language, wrong interpretation of the interlocutor’s reaction and assessment of the current situation